Advances in global leadership. volume 16 - Osland, Joyce S.; Reiche, B. Sebastian; Maznevski, Martha L.; Mendenhall, Mark E. (Advances in global leadership, 2025)
This volume in the Advances in Global Leadership series continues to advance both global leadership research and practice by bridging and integrating conceptual, empirical, and practitioner perspectives to provide a deeper understanding of this rapidly growing field of study. Volume 16 covers moral dilemmas, such as should businesses close operations in global conflict areas to avoid fuelling war or continue the operations to provide a livelihood for people in need? Responsible leadership in India is examined, especially with regards to indigenous perspectives on the emerging economy across the micro, meso, and macro levels of analysis. There is also ground-breaking research on transcultural competence, which questions the very definition of 'global' and an investigation of global leadership and AI. With its finger firmly on the pulse of this exciting field, this is a must-read book for scholars and practitioners alike.